Long-term Survival Based on the Surgical Approach to Lobectomy For Clinical Stage I Nonsmall Cell Lung Cancer: Comparison of Robotic, Video-assisted Thoracic Surgery, and Thoracotomy Lobectomy. Issue 2 (February 2017) - Yang, Hao-Xian; Woo, Kaitlin M.; Sima, Camelia S.; Bains, Manjit S.; Adusumilli, Prasad S.; Huang, James; Finley, David J.; Rizk, Nabil P.; Rusch, Valerie W.; Jones, David R.; Park, Bernard J.
Abstract : Objective: To compare the long-term outcomes among robotic, video-assisted thoracic surgery (VATS), and open lobectomy in stage I nonsmall cell lung cancer (NSCLC). Background: Survival comparisons between robotic, VATS, and open lobectomy in NSCLC have not yet been reported. Some studies have suggested that survival after VATS is superior, for unclear reasons. Methods: Three cohorts (robotic, VATS, and open) of clinical stage I NSCLC patients were matched by propensity score and compared to assess overall survival (OS) and disease-free survival (DFS). Univariate and multivariate analyses were performed to identify factors associated with the outcomes. Results: From January 2002 to December 2012, 470 unique patients (172 robotic, 141 VATS, and 157 open) were included in the analysis. The robotic approach harvested a higher number of median stations of lymph nodes (5 for robotic vs 3 for VATS vs 4 for open; P < 0.001). Patients undergoing minimally invasive approaches had shorter median length of hospital stay (4 d for robotic vs 4 d for VATS vs 5 d for open; P < 0.001). The 5-year OS for the robotic, VATS, and open matched groups were 77.6%, 73.5%, and 77.9%, respectively, without a statistically significant difference; corresponding 5-year DFS were 72.7%, 65.5%, and 69.0%, respectively, with a statistically significant difference between the robotic and VATS groups ( P = 0.047). However, multivariate analysis found that surgical approach was not independently associated with shorter OS and DFS. Conclusions: Minimally invasive approaches to lobectomy for clinical stage I NSCLC result in similar long-term survival as thoracotomy. Use of VATS and robotics is associated with shorter length of stay, and the robotic approach resulted in greater lymph node assessment. Abstract : Supplemental Digital Content is available in the text